2007
DOI: 10.1124/dmd.107.016345
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Radiometric CYP2C19 Inhibition Assay Using Tritiated (S)-Mephenytoin

Abstract: ABSTRACT:A rapid and sensitive radiometric assay for assessing the potential of drugs to inhibit cytochrome P450 (P450) 2C19 in human liver microsomes is described. The new assay, which does not require high-performance liquid chromatography (HPLC) separation or mass spectrometric detection, is based on the release of tritium as tritiated water that occurs upon CYP2C19-mediated 4-hydroxylation of (S)-mephenytoin labeled with tritium in the 4 position. Because this reaction is subject to an NIH shift, tritium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Whereas almost linear dependence was estimated during the studied period for the lower concentration of CYP2C9, a slight nonlinearity was found at higher CYP2C9 concentration. Similar behaviour was recently observed by Di Marco et al [29] by means of a radiometric CYP2C9 assay. A range of CYP2C9 concentrations was tested as well.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Whereas almost linear dependence was estimated during the studied period for the lower concentration of CYP2C9, a slight nonlinearity was found at higher CYP2C9 concentration. Similar behaviour was recently observed by Di Marco et al [29] by means of a radiometric CYP2C9 assay. A range of CYP2C9 concentrations was tested as well.…”
Section: Resultssupporting
confidence: 78%
“…As mentioned above, Di Marco et al [29] published recently a highly sensitive radiometric method for monitoring the CYP2C9 activity with diclofenac. This assay is based on the release of tritium as tritiated water from the diclofenac labelled with tritium in the 4 0 -position.…”
Section: Resultsmentioning
confidence: 96%
“…Based on the results described herein, it is concluded that EE is not a submicromolar inhibitor of human P450s in vitro (Table 3). The lack of submicromolar inhibition of CYP2C19 Rodrigues and Lu, 2004;Di Marco et al, 2007), CYP2C8 (Walsky et al, 2005), CYP2C9 , CYP2B6 (Walsky et al, 2006), and CYP1A2 (Karjalainen et al, 2008) activity in vitro is consistent with the literature. To our knowledge, however, this is the first report describing the assessment of EE as an in vitro inhibitor of CYP2J2, CYP2D6, CYP1B1, and CYP1A1.…”
Section: Discussionsupporting
confidence: 79%
“…Other authors have reported IC 50 s for (S)-mephenytoin with HLM in the range of ϳ3.5 to 20 M, although no attempt was made to correct for microsomal binding (Rodrigues and Lu, 2004;Di Marco et al, 2007). To date, all the reported K i and IC 50 values for CYP2C19 are still considerably higher than the calculated total concentration of EE in enterocytes (ϳ6.0 nM) and hepatic portal vein (ϳ0.4 nM).…”
Section: Discussionmentioning
confidence: 86%
“…The concentrations of the secondary amines in the inactivation assays and estimates of reversible affinities for their respective enzymes were as follows: DES ϭ 50 M with CYP2C11 (IC 50 ϭ 5 M, data not shown), (S)-FLX ϭ 10 M with CYP2C19 (IC 50 ϭ 4.7 M in HLMs) (Di Marco et al, 2007), and MA ϭ 2 M with CYP3A4 (K i ϭ 2 M in HLMs) (Zhao et al, 2007). The secondary hydroxylamine substrate concentrations used were lower to facilitate data acquisition and curve-fitting: DESOH ϭ 1 M, (S)-FLXOH ϭ 5 M, and MAOH ϭ 0.5 M. The initial rates of the loss of enzyme activity caused by the secondary amines and secondary hydroxylamines were determined in triplicate in the presence and absence of fixed concentrations of the primary amines at their respective K i or IC 50 values.…”
Section: Downloaded Frommentioning
confidence: 99%